Isolation and characterization of arsenic resistant soil bacteria and their effects on germination of rice under arsenic contamination - Ahmed, Istiaq; Islam, Md Tofazzal; Chowdhury, Md Akhter Hossain; Kamruzzaman, Md (Research in Agriculture Livestock and Fisheries, 2015)
This study was carried out to isolate, screen and characterize arsenic (As) resistant bacteria from As contaminated soils of Dumrakandi and Matlab under Faridpur and Chandpur districts and to evaluate their efficiency in reducing As toxicity against rice seedlings during germination. Thirteen strains were isolated from the soils which showed resistance to different levels of sodium arsenite (viz. 5, 10, 20 and 40 mM) in both agar plate and broth assay using BSMY I media. Among the isolates, BTL0011, BTL0012, BTL0015 and BTL0022 showed highest resistance to 40 mM sodium arsenite. Gram staining and KOH solubility test revealed that five strains were gram positive and rest eight was gram negative. They grew well in the liquid media at pH 5.5 to 8.5. In-vitro rice seedling bioassay with two superior isolates (BTL0011 and BTL0022) revealed that As resistant strains significantly enhanced seed germination of BRRI dhan29 and BRRI dhan47 at 60 ppm As. This study was laid out in CRD with three replications. The performance of BTL 0022 was superior to BTL0011. The overall results suggest that BTL0011 and BTL0022 can be used for bioremediation of As contaminated soils and to increase the germination and seedling growth of rice in As contaminated soils. Res. Agric., Livest. Fish.2(2): 229-237, August 2015